Paradictyocheirospora tectonae, a novel genus in the family Dictyosporiaceae from India - Rajeshkumar, Kunhiraman C.; Verma, Rajnish K.; Boonmee, Saranyaphat; Chandrasiri, Sajini; Hyde, Kevin D.; Ashtekar, Nikhil; Lad, Sneha; Wijayawardene, Nalin N. (Phytotaxa, 2021)
This study introduces, Paradictyocheirospora, a new genus, belonging to the family Dictyosporiaceae with evidence from morphology and phylogenetic analysis of a combined ITS, LSU and TEF1α sequence data. Paradictyocheirospora can be distinguished from allied taxa based on dictyosporous, cheiroid conidia with suprabasal bubble-like hyaline appendages and cylindrical, reduced conidiophores. The new genus is similar to Dictyocheirospora; however, the conidia are smaller with fewer rows (3–6) and have globose, supra-basal appendages. Paradictyocheirospora tectonae forms a distinct lineage basal to Digitodesmium and Dictyocheirospora. Additional new collections from Thane, Maharashtra were morphologically identical and phylogenetically related to Dictyocheirospora nabanheensis, and the latter is a new record from India.